Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Southern Noatak Valley, Alaska - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
As part of the Perma-X airborne campaign led by the Alfred Wegener Institute in 2021, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 20 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates four data subsets of the southern Noatak Valley, Alaska, covering approximately 110 km². All images were collected on 2 July 2021.
Keywords: Airborne Data; Alaska; Arctic Landscape Dynamics; Digital Surface Model; MACS; Orthoimagery; Permafrost; point clouds; Structure-from-Motion